2021
DOI: 10.1007/s10389-021-01487-0
|View full text |Cite
|
Sign up to set email alerts
|

Chronically unprepared: emergency preparedness status among US medically vulnerable populations

Abstract: Background The prevalence of large-scale natural and biological disasters has increased in recent years and can have detrimental impacts on health. Some populations are more susceptible to these impacts, including medically vulnerable populations. The purpose of this study was to evaluate the association between medically vulnerable populations and perceived emergency preparedness status. Methods This study used 2010 and 2012 Behavioral Risk Factor Surveillance System data (n = 33,852). Participants were class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…Our report summarizes hypertension control strategies that MH Exemplars implemented in response to the disruptions to routine medical care during the COVID-19 pandemic. Data support the fact that frequent interactions with clinical staff are essential to chronic disease management and during temporary disruptions in access to health care for hypertensive patients when a natural disaster results in increased rates of uncontrolled hypertension (12).…”
Section: Implications For Public Healthmentioning
confidence: 77%
See 1 more Smart Citation
“…Our report summarizes hypertension control strategies that MH Exemplars implemented in response to the disruptions to routine medical care during the COVID-19 pandemic. Data support the fact that frequent interactions with clinical staff are essential to chronic disease management and during temporary disruptions in access to health care for hypertensive patients when a natural disaster results in increased rates of uncontrolled hypertension (12).…”
Section: Implications For Public Healthmentioning
confidence: 77%
“…Patients with existing medical conditions have experienced poor outcomes in the setting of an emergency, including difficulty accessing emergency services and routine care (13). People living with chronic diseases, including hypertension, are at an increased risk of adverse health outcomes in the face of public health emergencies, and this risk increases exponentially with a prolonged crisis (12). Many communities are not adequately prepared to meet the needs of people living with chronic diseases during a public health emergency.…”
Section: Implications For Public Healthmentioning
confidence: 99%
“…The effects of gender and age on emergency preparedness have been inconsistent in research. Some studies found that women were less prone to prepare for emergencies than men [18,22,30]. But an Israeli study found that females showed signi cantly higher preparedness levels than male participants [4].…”
Section: Discussionmentioning
confidence: 99%
“…Penyertaan sumber daya yang terkait dengan populasi rentan dalam agenda pelatihan tambahan merupakan kebutuhan mendesak. Perlu dicatat bahwa kelompok kolaborasi ini terus melanjutkan pekerjaannya dan kebutuhan tambahan untuk populasi yang rentan akan ditangani (Barbato et al, 2022).…”
Section: Hasil Dan Pembahasanunclassified